2021
DOI: 10.3390/su132413736
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress Affects the Some Morpho-Physiological Traits of Twenty Wheat (Triticum aestivum L.) Genotypes under Field Condition

Abstract: Water stress has become one of the foremost constraints to agricultural development, mostly in areas that are deficient in water. A field trial has been conducted to evaluate the performance of different twenty wheat genotypes under three stress treatments viz., control (T0) = normal watering, stress-1 (T1) = water stress from tillering up to maturity, and stress-2 (T2) = water stress from anthesis to maturity were used as treatments. The results revealed that a highly significant (p < 0.01) difference was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A combined effect of drought and heat stress is more detrimental than individual stresses [21]. Wheat shows the highest susceptibility under water stress from tillering to maturity [22]. Zhang et al [23] report that the reductions in common wheat yield under mild, moderate, and severe stress were 21.0%, 25.8%, and 32.0%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A combined effect of drought and heat stress is more detrimental than individual stresses [21]. Wheat shows the highest susceptibility under water stress from tillering to maturity [22]. Zhang et al [23] report that the reductions in common wheat yield under mild, moderate, and severe stress were 21.0%, 25.8%, and 32.0%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Drought-tolerant wheat cultivars in this experiment have higher leaf chlorophyll content and quantum yield of PSII than sensitive genotypes (Figures 3G, H) producing high yield under drought stress, indicating a positive correlation between chlorophyll content, quantum yield of PSII, and crop yield, in accordance with findings of Chowdhury et al (2021) and Bano et al (2021) that droughttolerant wheat cultivars have greater chlorophyll content and quantum yield. Wasaya et al (2021) noted a reduction in spike length, number of grains per spike, and grain weight under drought stress in wheat cultivars, while a reduction in the number of tillers per plant, number of spikelet per spike, and number of grains per spike was observed by Panhwar et al (2021). The results obtained from the present research suggest that Barani-83, Blue Silver, Pak-81, and Pasban-90 showed better response towards drought conditions, while FSD-08, Lasani-08, Punjab-96, and Sahar-06 cultivars showed poor performance in terms of yield attributes such as the decline in grain yield and 100 grain weight under water shortage is due to reduced production of photoassimilates and their reduced absorption by sink while the reduction in the number of grains per spike was due to loss of pollen viability as explained in earlier studies by Chowdhury et al (2021).…”
Section: Discussionmentioning
confidence: 96%
“… Wasaya et al. (2021) noted a reduction in spike length, number of grains per spike, and grain weight under drought stress in wheat cultivars, while a reduction in the number of tillers per plant, number of spikelet per spike, and number of grains per spike was observed by Panhwar et al. (2021) .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have demonstrated that water deficit stress has a significant impact on different growth stages of wheat plants, including tillering, stem elongation, heading, anthesis, and grain filling. The yield components that contribute to the final grain yield (GY) vary at each growth stage, and the severity of the water deficit stress depends on how these components are impacted [ 60 , 61 , 62 , 63 , 64 ]. The final GY of wheat is determined by the number of tillers and spikes per plant, the number of spikelets per spike, and the number and weight of grains per spike [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%